COMPARATIVE STUDY BETWEEN GHUNYAT-UL-QARI SHARAH SAHIH-UL-BUKHARI AND KASHF-UL-BARIIN THE INTERPRETATION OF THE TITLES OF THEIR BOOKS - Maaz Masood; Dr. Gulzar Ali; Dr. Muhammad Kamran (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Sahih Ul-Bukhari has the highest position and status in the books of hadiths, due to this importance, a large number of scholars paid attention to its interpretation, one of them is Maulana Abdul Khaliq Bajuri who wrote a book called "Ghunyat Ul-Qari Sharh Sahih Ul-Bukhari". In this Commentary, he has collected a lot of information which is the best guide for students of hadiths. In this article, Maulana Abdul Khaliq Bajuri's manner and style in interpreting the titles of books in the fifteenth volume of the said commentary has been discussed. This manual consists of seven points which include lexical research, terminological research, explanation of various terminological meanings, interpretation with poems and answers to objections.